(untitled) (Teaching and Learning Inquiry, 2019)
At the conference of the International Society for the Scholarship of Teaching and Learning (ISSOTL) in Bergen, Norway (October 2018), we were privileged to have heard a lecture by Elizabeth Minnich, “People who are not thinking are capable of anything: What are students learning, how are students learning it, and does it make them better people?” In November 2018, as a follow-up to the lecture, Chng Huang Hoon (then ISSOTL vice president, Asia Pacific) invited the ISSOTL community to pose the questions to Professor Minnich. Questions from four members—John Draeger, Torgny Roxå, Johan Geertsema, and Chng Huang Hoon—were received. Professor Minnich emailed her responses to each question, and over the next six months there ensued several email exchanges between each contributor and Professor Minnich, which resulted in the first draft of this conversation. With the help of the above contributors, Huang Hoon wove the separate pairs of exchanges into this conversation, which not only addresses points in her keynote in Bergen but also discusses issues in her works. Teaching & Learning Inquiry has generously provided this platform for sharing the conversation. We hope TLI readers will benefit from this effort and we welcome readers to continue the discussion.